2022
DOI: 10.1080/21655979.2022.2044278
|View full text |Cite
|
Sign up to set email alerts
|

The role of human mast cells in allergy and asthma

Abstract: Mast cells are tissue-inhabiting cells that play an important role in inflammatory diseases of the airway tract. Mast cells arise in the bone marrow as progenitor cells and complete their differentiation in tissues exposed to the external environment, such as the skin and respiratory tract, and are among the first to respond to bacterial and parasitic infections. Mast cells express a variety of receptors that enable them to respond to a wide range of stimulants, including the high-affinity FcεRI receptor. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 129 publications
2
25
0
Order By: Relevance
“…In our study, long-term cognition was impaired by GA administration at PND 7 (the peak of synaptogenesis), and DSCG provided long-lasting protection until early adulthood. Mast cells act as the first immune-related responders in the brain and can lead to the release of inflammatory factors through degranulation (Banafea et al, 2022). In this study, we demonstrated that MCs can promote the development of hippocampal inflammation after early GA exposure.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our study, long-term cognition was impaired by GA administration at PND 7 (the peak of synaptogenesis), and DSCG provided long-lasting protection until early adulthood. Mast cells act as the first immune-related responders in the brain and can lead to the release of inflammatory factors through degranulation (Banafea et al, 2022). In this study, we demonstrated that MCs can promote the development of hippocampal inflammation after early GA exposure.…”
Section: Discussionsupporting
confidence: 52%
“…Mast cells act as the first immune-related responders in the brain and can lead to the release of inflammatory factors through degranulation ( Banafea et al, 2022 ). In this study, we demonstrated that MCs can promote the development of hippocampal inflammation after early GA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Once the MCs and the basophils are activated, multiple signaling cascades are produced precipitating biochemical reactions responsible for the degranulation and release of vasoactive mediators, enzymes, and cytokines contained inside the cells. These mediators are released locally and into the circulatory system, causing bronchoconstriction and increased vascular permeability leading to urticaria, angioedema, and hypotension, among other actions [ 32 ]. These mediators are classified as preformed mediators or de novo synthesized lipid mediators (Fig.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Overall, MCs play both protective and pathological roles: they contribute to tissue repair, deactivation of proinflammatory cytokines, lympho-angiogenesis, smooth muscle relaxation, and negative feedback with immunomodulant functions; on the other hand, MCs provoke muscle contraction, immune cell infiltration, airway barrier disruption, airway remodeling, fibrosis, and increase mucus production [60]. In this article, the focus has been put on the two main MC-related airway diseases, respectively from upper and lower airways: rhinitis (with a particular interest in allergic rhinitis) and asthma.…”
Section: Mast Cells In the Airwaymentioning
confidence: 99%